The war in Italy 1943-1944 - Mace, Martin; Grehan, John; Mitchell, Sara (Military history researcher) (Despatches from the front, 2014)
Despatches in this volume include that on the Conquest of Sicily from 10 July 1942 to 17 August 1943 by Field-Marshall Viscount Alexander of Tunis; the despatch on the invasion of Sicily in July 1943, by Admiral of the Fleet Sir Andrew B. Cunningham, Commander-in-Chief, Mediterranean; despatch on naval operations in connection with the landings in the Gulf of Salerno in September 1943, by Admiral of the Fleet Sir Andrew B. Cunningham; and the despatch on operations of the Allied Armies between September 1943 and December 1944, by Field Marshal the Viscount Alexander of Tunis. This unique collection of original documents will prove to be an invaluable resource for historians, students and all those interested in what was one of the most significant periods in British military history.